Human Amniotic Epithelial Cells Secretome: Components, Bioactivity, and Challenges - Fathi, Ibrahim; Miki, Toshio (Frontiers in Medicine, 2022)
Human amniotic epithelial cells (hAEC) derived from placental tissue have received significant attention as a promising tool in regenerative medicine. Several studies demonstrated their anti-inflammatory, anti-fibrotic, and tissue repair potentials. These effects were further shown to be retained in the conditioned medium of hAEC, suggesting their paracrine nature. The concept of utilizing the hAEC secretome has thus evolved as a therapeutic cell-free option. In this article, we review the different components and constituents of hAEC secretome and their influence as demonstrated through experimental studies in the current literature. Studies examining the effects of conditioned medium, exosomes, miRNA derived from hAEC are included in this review. The challenges facing the application of this cell-free approach will also be discussed based on the current evidence.